PERLINDUNGAN HUKUM BAGI PEMBELI PADA PT. NEW VILLA GREEN PADAT KARYA INDAH JALAN PADAT KARYA LOA BAKUNG KOTA SAMARINDA (PERUMAHAN UNIT TERBATAS) - Aldila Wijayanti Putri (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTHousing as one of the basic needs in humans, both as a unit with fellow natural environment. This natural relationship is the place to be and at the same time the means that support and provide the materials needed for property ownership as regulated in the 1945 Constitution in chapter X, which is included in Human Rights which has regulated those relating to property ownership as contained in Article 27 Paragraph 1 which reads: "every citizen has the right to move, move and reside in the territory of the Republic of Indonesia". Article which reads: "everyone has the right to live and live a decent life". Human social beings are always in contact with other humans, the interactions that only occur in communication do not have human and socio-cultural dimensions, but also involve legal aspects, including Civil Law. In this research, the type of research used is normative legal research or library law research because it is in the form of secondary data such as legislation and literature books, in this study the method of accessing and research is mostly taken from library materials, namely materials that contain scientific knowledge. new or up-to-date, or new understandings of known facts or ideas, in this case including books, journals, dissertations or theses and other legal materials. This normative legal research material fully uses primary legal materials and secondary legal materials.Development usually has several considerations in determining the price to sell the house, such as the location of the house which is strategically located, having architects and workers who are experts in house construction, being able to complete the construction of the house exactly as agreed.Article 18 paragraph (1) of the consumer protection law states that business actors are prohibited from including standard clauses in agreements regarding giving rights to business actors to reduce the benefits of services or reduce the assets and assets of consumers who are the object of buyig and selling services.